Potassium irrigation and fertigation of grapevine under semiarid conditions - Albuquerque, André Henrique Pinheiro (2013)
The potassium irrigation management and fertigation adjustment may improve grape yield and quality. Aiming at evaluating the biometric and productive characteristics of the ‘Ribier’ grapevine, under five irrigation levels (50%, 75%, 100%, 125% and 150% of the class A pan evaporation - CAE) and five potassium fertilization doses (2, 4, 6, 8 and 10 days), applied by fertigation, two experiments were carried out in a randomized blocks design, with five treatments and five replications, in Limoeiro do Norte, Ceará State, Brazil. The variables bunch number, size and average weight, soluble solids and yield were evaluated for the five irrigation levels, while the bunch average weight and width, number of berries, soluble solids and yield were evaluated for the five potassium fertigation intervals. The maximum irrigation level (150% of the CAE) and the seven days interval for the potassium fertigations provided the best yield for the ‘Ribier’ grapevine, under the Ceará State semiarid conditions.